Population-based laboratory surveillance of imported malaria in metropolitan Calgary, 2000-2011. - Clara S Lee (PLoS ONE, 2013)
Increased travel leads to a heightened risk of imported infectious diseases. Patterns of immigration to countries like Canada have changed such that countries of malaria endemicity are frequented in larger numbers. In keeping with the changes in travel patterns and immigration, the major metropolitan city of Calgary has seen a dramatic rise in malaria incidence over the last decade. Fuelling this rise in Calgary has been the apparent complacence with prophylaxis in individuals visiting friends and relatives and potentially inadequate public health intervention in areas of the city with increased immigration and lower socioeconomic status.